2013
DOI: 10.5851/kosfa.2013.33.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Wild Grape on the Antioxidative Potential of the Breast and Leg Meat of Broilers

Abstract: This study investigated the effect of wild grape (Vitis coignetiae) dietary supplementation on the antioxidative potential and quality of the breast and leg meat of broilers. A total of 36 one-day-old male Cobb broiler chicks were obtained from a commercial hatchery, and randomly assigned to 9 pens with 4 birds per pen. Then, broilers were fed 3 different dietary supplementations, including 0%, 0.25%, or 0.5% wild grape, for 2 wks at the finishing period. After slaughtering, the total phenolic content, α,α'-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
3
0
0
Order By: Relevance
“…The significant reduction of cholesterol in broiler meat due to supplementation of Moringa oleifera pods meal in feed might be attributed to phytosterols (β-sitosterol) present in the Moringa plant tissues, which decreases the absorption of cholesterol from the intestine with an immediate release in the feces. Similar results haven reported in many other studies where diet was manipulated with antioxidants and plant tissue material and cholesterol level was lowered [37][38][39][40] . The linear increase in the selenium level of breast meat samples in commercial broilers may be attributed to the higher selenium content in Moringa pod meal supplemented feed.…”
Section: Discussionsupporting
confidence: 89%
“…The significant reduction of cholesterol in broiler meat due to supplementation of Moringa oleifera pods meal in feed might be attributed to phytosterols (β-sitosterol) present in the Moringa plant tissues, which decreases the absorption of cholesterol from the intestine with an immediate release in the feces. Similar results haven reported in many other studies where diet was manipulated with antioxidants and plant tissue material and cholesterol level was lowered [37][38][39][40] . The linear increase in the selenium level of breast meat samples in commercial broilers may be attributed to the higher selenium content in Moringa pod meal supplemented feed.…”
Section: Discussionsupporting
confidence: 89%
“…Polyphenol content observed in the control patties and in those formulated with grape by-products was similar to that found by other authors in patties enriched with fruit extracts (Devatkal et al, 2010) and in the thigh meat of broilers fed wild grapes (Yong et al, 2013). However, polyphenol content in the patties of this study was lower than that observed by other authors in low-salt meat pork emulsion containing seaweed (López-López et al, 2009) and walnut (Ayo et al, 2007).…”
Section: Total Extractable Polyphenolic Compoundssupporting
confidence: 88%
“…The lack of differences in TBA values in pectoral muscles of chickens fed diets enriched with 3 and 6% of apple, BC, or strawberry pomace were previously reported by Colombino et al [20]. Also, Yong et al [44] indicated that feeding broilers diet with grape powder significantly extended total phenolic content in the leg meat, with no differences detected in breast meat.…”
Section: Effects Of the Polyphenolic Supplements On Oxidative Stability Of The Meatsupporting
confidence: 51%